Afmeting excl. passe-partout. . Titel prent: Dr. Kuypers zorg voor de kleine luyden : in den naam van Christus! - Hahn, Albert
Afmeting excl. passe-partout. Titel prent: Dr. Kuypers zorg voor de kleine luyden : in den naam van Christus!.